What makes an individual inclusive of others? Development of the individual inclusiveness inventory - Josten, Cecily; Lordan, Grace (Frontiers in Psychology, 2025)
IntroductionCollaboration and inclusion are key drivers of successful work outcomes in today’s increasingly diverse workforce. Yet, while organizational inclusion has been widely studied, less is known about what makes an individual inclusive of others at work. We define an inclusive individual as someone who actively includes others in a group, values diversity of thought and background, and fosters group performance and productivity. To address this gap, we develop and validate a new measure: the Individual Inclusiveness Inventory.MethodsUsing a combined deductive and inductive approach, we generated scale items based on a review of the inclusion literature and qualitative interviews with 14 diversity and inclusion experts. We conducted exploratory factor analysis (EFA) followed by confirmatory factor analysis (CFA) on responses from two samples of working professionals in the UK.ResultsThe analyses revealed a two-factor solution. The first factor, Belonging and Uniqueness, captures the ability to foster a sense of belonging while valuing individuals’ distinctiveness. The second factor, Challenge and Openness, reflects openness to diverse perspectives and willingness to engage in and accept constructive challenge. Both factors demonstrated good reliability. Predictive validity analyses showed that Challenge and Openness was positively associated with all measured work outcomes, including income. Belonging and Uniqueness was positively associated with the number of people managed, perceived seniority, and happiness at work.DiscussionOur findings suggest that individual inclusiveness is multi-dimensional and differentially predictive of work outcomes. Challenge and Openness appears closely linked to productivityrelated outcomes, likely due to its association with innovation and competitiveness. Belonging and Uniqueness, while less predictive of productivity, is important for relational outcomes such as team cohesion and well-being. These insights have implications for talent development and inclusive leadership training.